The Effect of Job Insecurity on Turnover Intention Mediated by Job Satisfaction at PT. Indocitra Jaya Samudera - Ni Made Putri Gangga Pratiwi; Ida Bagus Ketut Surya (International Journal of Economics, Management and Accounting, 2025)
Job insecurity is a psychological condition that can lead to emotional instability among employees, ultimately increasing their intention to leave the organization. Job satisfaction is suspected to act as a mediating variable that can mitigate the negative impact of job insecurity on turnover intention. This study aims to analyze the effect of job insecurity on turnover intention, mediated by job satisfaction, at PT Indocitra Jaya Samudera. A quantitative method with a causal associative approach was employed. The population consisted of 298 employees, and a sample of 171 respondents was selected using stratified sampling. Data analysis was conducted using Partial Least Squares (PLS) to examine the relationships between variables. The results show that job insecurity has a positive and significant effect on turnover intention, a negative effect on job satisfaction, and that job satisfaction negatively and significantly affects turnover intention. Furthermore, the mediation analysis indicates that job satisfaction mediates the relationship between job insecurity and turnover intention.